Unmasking the rising global burden of depression: A 32-year GBD analysis of gender disparities and regional hotspots in Sub-Saharan Africa - Junping Liu; Zhongming Ye; Yan Cai; Jiaying Li; Zhe Dong; Xiaodan Zhang; Ming Lei (PLoS ONE, 2025)
Aims Depression, a leading contributor to the global disease burden, exhibits alarming increases in incidence and prevalence, with pronounced disparities across regions and genders. This study provides the first comprehensive analysis of depression burden from 1990 to 2021, integrating the latest Global Burden of Disease (GBD) 2021 data to identify critical hotspots and policy-relevant trends. Methods Estimated global, regional, and national burden of disease for depression from 1990–2021 by extracting incidence, prevalence, and DALYS from the Global Burden of Disease(GBD) database 2021. Results From 1990 to 2021, the global incidence of depression surged by 15.6% (3,749–4,334 per 100,000), with Sub-Saharan Africa emerging as an unexpected epicenter. Uganda and The Gambia recorded the highest incidence rates globally (9,644 and 7,624 per 100,000, respectively), likely linked to civil instability and healthcare deficits. Women bore a disproportionate burden, with adolescent females (15–19 years) showing 64% higher incidence than males (5,584 vs. 3,401 per 100,000). High-income regions paradoxically exhibited steeper annual percentage increases (EAPC: 1.0 in North America), suggesting improved detection or escalating stressors. Conclusions This study highlights urgent priorities: (1) integrating mental health services into primary care in conflict-affected African nations. (2) gender-sensitive interventions targeting adolescent females. (3) global equity in mental health resource allocation.